The impact of genital warts: loss of quality of life and cost of treatment in eight sexual health clinics in the UK. Issue 6 (2nd June 2011) - Woodhall, S C; Jit, M; Soldan, K; Kinghorn, G; Gilson, R; Nathan, M; Ross, J D; Lacey, C J N
Abstract : Objectives: To estimate the loss of quality of life and cost of treatment associated with genital warts seen in sexual health clinics. Methods: A cross-sectional questionnaire study and case note review of individuals with genital warts, carried out in eight sexual health clinics in England and Northern Ireland. Individuals with genital warts attending the participating clinics were invited to take part in the questionnaire study. 895 participants were recruited. A separate sample of 370 participants who had attended a participating clinic with a first visit for a first or recurrent episode of genital warts between April and June 2007 was included in the case note review. Quality of life was measured using the EQ-5D questionnaire and the cost of an episode of care was derived from the case note review. Results: The weighted mean EQ-5D index score was 0.87 (95% CI 0.85 to 0.89). The weighted mean disutility was 0.056 (95% CI 0.038 to 0.074). The estimated mean loss of quality-adjusted life-years associated with an episode of genital warts was 0.018 (95% CI 0.0079 to 0.031), equivalent to 6.6 days of healthy life lost per episode. The weighted mean cost per episode of care was £94 (95% CI £84 to £104), not including the cost of a sexually transmitted infection screen. Conclusions: Genital warts have a substantial impact on the health service and the individual. This information can be utilised for economic evaluation of human papillomavirus vaccination.